"ASSESSING THE IMPACT OF REMITTANCES FROM OVERSEAS WORKERS ON POVERTY IN LEBANON (2001-2023)" - Mukhlaf, Asmaa Taha (The journal of contemporary issues in business and government, 2024)
Remittances from migrants constitute an important source of income in Lebanon, especially during economic crises. Between 2001 and 2023, remittances increased and accounted for about 14% of GDP in 2021. Studies indicate that remittances contribute to reducing poverty and improving living conditions by financing education and healthcare. For instance, a 2006 study showed that 24.6% of Lebanese households were deprived of basic necessities, but households receiving remittances managed to improve their financial and social status. The study used semi-annual data from Lebanon to analyze the relationship between remittances and poverty using statistical models such as unit root tests and co-integration analysis. The results showed that remittances significantly reduce poverty and improve economic conditions, aligning with previous literature that confirms the role of remittances in enhancing household income and access to education and healthcare. The study recommends enhancing financial inclusion and reducing remittance costs, developing policies to invest remittances in productive projects, and strengthening social safety nets to support vulnerable groups. The study summarizes the impact of remittances on poverty alleviation in Lebanon and the importance of their role in supporting the economy and improving living conditions .